ION-INDUCED SECONDARY ELECTRON EMISSION FROM 58Ni AND 60Ni: EVIDENCE OF SECONDARY ELECTRONS GENERATED BY THE RECOILING TARGET ATOMS - Ullah, Shakir; Dogar, A. H.; Qayyum, A. (The Nucleus, 2010)
We have measured the secondary electron yield of clean 58Ni and 60Ni bombarded with 2-10 keV Ar + ions. It was found that secondary electron yield of 58Ni is consistently high as compared to the 60Ni. This result is not in line with the most theoretical model of kinetic electron emission, which predict strict proportionality between secondary electron yield and electronic stopping power. We have demonstrated that the measured secondary electron yield is also related to the nuclear stopping power. We thus conclude that higher secondary electron yield of 58Ni is due to the larger contribution of the recoiling target atoms to the secondary electron yield.